Primary health care. The Peruvian experience - Carbone Campoverde, Fernando Ignacio (2018)
Alma Ata is still in force in those experiences of comprehensive health care from all and for all that some countries have managed to implement, especially in the rural areas with populations affected by exclusion and poverty. Peru has several of them that find their roots in experiences previous to the 1978 Conference. It is interesting to confirm that many of these were initially dedicated to the care of pregnant women and newborns, and then they have translated their lessons learned to the care of the whole population.